Improving SME access to public procurement : the experience of selected countries (ITC GenevaCH, 2000)
Focuses on the role of government programmes in public procurement to assist small and medium-sized enterprises (SMEs) in becoming better exporters. Identifies and explains advantages and disadvantages of public procurement programmes designed to assist SMES. Looks at criteria used for determining eligibility for SME status in various countries. Examines programmes used by selected countries to assist SMEs in a procurement context. Gives guidance on implementation of public procurement programmes designed to assist SMEs.
Keywords: SMALL ENTERPRISES